Steppe Eagle's Population Structure Migrating Through The Bottleneck Of Eilat In Spring - Noam Weiss (Пернатые хищники и их охрана)
Steppe Eagles (Aquila nipalensis) migrate in large numbers past key migration flyways from almost its entire breeding region. On its spring migration route from Africa many birds fly through the bottleneck of Eilat in southern Israel. Migration timing and age structures in the population are often key elements of conservation works. In the four springs of 2015 to 2018 we systematically counted the passing Steppe Eagles at two count stations. An average of 15,039 Steppe Eagles were counted per spring. We also recorded the ages of many of the Eagles.